2014
DOI: 10.14202/vetworld.2014.601-604
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on incidence of lameness in domestic animals

Abstract: A retrospective study on incidence of lameness in domestic animals, 7(8): 601-604. Veterinary World IntroductionLameness is defined as an abnormal stance or gait caused by either a structural or a functional disorder of the locomotor system [1]. A variety of reasons for lameness have been reported, including heritable defects, congenital defects, developmental defects, growth defects, trauma, and infection. Lameness is very common in dogs due to their active nature. Musculoskeletal disorders are found to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…The highest prevalence of lameness was in animals of above 5 years (13.3%), followed by those between 3 -5 years (10.9%), 1 -3 years (10.3%) and <1 year (9.6%) ( Table 2). This result is in conformity with the results Mohsina et al (2014).…”
Section: Prevalence Of Lameness With Respect To Age In Cattlesupporting
confidence: 94%
“…The highest prevalence of lameness was in animals of above 5 years (13.3%), followed by those between 3 -5 years (10.9%), 1 -3 years (10.3%) and <1 year (9.6%) ( Table 2). This result is in conformity with the results Mohsina et al (2014).…”
Section: Prevalence Of Lameness With Respect To Age In Cattlesupporting
confidence: 94%
“…The incidence of lameness in dairy animals reared under modern housing conditions is relatively high, which could be explained by their reduced physical activity (Stafford & Gregory, ). Lameness affecting the buffalo hind foot is frequently encountered in veterinary practice, either due to primary causes in the foot itself or secondary to disease conditions affecting other parts of the limb, for example upward fixation of the patella (Barbosa et al, ; Mohsina et al, ; Shivaprakash & Usturge, ). In the current study, the appearance of buffalo hind foot was described using low‐field T1‐W and T2‐W MRI scans and validated using corresponding gross anatomical sections.…”
Section: Discussionmentioning
confidence: 99%
“…3). Mohsina et al, (2014) in their study on incidence of lameness in different species observed hip dislocation (6%) as a cause of lameness in dogs. Neurological affection was observed only in canine (n=12) ( Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…Neurological affection was observed only in canine (n=12) ( Table 2). Mohsina et al, (2014) has opined that dogs often suffer from lameness due to their active nature. Scott and Witte (2011) have stated that lameness in dog occur more commonly due to musculoskeletal disorder than neurological.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation